2022
DOI: 10.1051/e3sconf/202236001019
|View full text |Cite
|
Sign up to set email alerts
|

Study on the influence of different test cycles on vehicle emission and fuel consumption

Abstract: In order to satisfy regulations of CHINA 6 and the corresponding standards of fuel consumption, a variety of advanced technology are adopted. While manufacture calibrate engine based on WLTC and NEDC test cycle during development process, and the technical route is still a lack of a large number of test research on CLTC. This article firstly investigates mainstream technology on market, then in-depth study influence of different test cycle on emissions and fuel consumption, comparing difference of test data to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Based on this background, the MIIT (Ministry of Industry and Information Technology) of China developed its own driving cycle named CLTC-P (China Light-duty Vehicle Test Cycle) for fuel consumption certi cation in 2015 (Liu et al 2020), which would be used to measure CO 2 emissions.. Wang et al (2022c) found that the average deviation of fuel consumption under the NEDC was 22%, under the WLTC was 17%, and under the CLTC-P was 10% when examining the average fuel consumption of various models from users through the platform 'Bear Check Fuel Consumption'. This indicated that the CLTC-P has more realistic and transient tra c patterns, making it more suitable for Chinese roads.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this background, the MIIT (Ministry of Industry and Information Technology) of China developed its own driving cycle named CLTC-P (China Light-duty Vehicle Test Cycle) for fuel consumption certi cation in 2015 (Liu et al 2020), which would be used to measure CO 2 emissions.. Wang et al (2022c) found that the average deviation of fuel consumption under the NEDC was 22%, under the WLTC was 17%, and under the CLTC-P was 10% when examining the average fuel consumption of various models from users through the platform 'Bear Check Fuel Consumption'. This indicated that the CLTC-P has more realistic and transient tra c patterns, making it more suitable for Chinese roads.…”
Section: Introductionmentioning
confidence: 99%